Sources of information on Medicines in Family Medicine - Santiago, Luiz Miguel (2006)
Background: General Practice is a broad-spectrum medical speciality, requiring thorough information. Mostly, information on medicines is crucial. Aim: To study the information sources on drugs and therapeutics among General Practitioners of the Centre Region of Portugal; Methods: Cross-sectional study in a sample of General Practitioners in ambulatory primary care setting; 50% of the Health Centres of the Central Region of Portugal were invited to answer a simple questionnaire, after a random stratified process of choice of Health Centres in each geographical district. Results: A sample of 317 (17,6% of the total medical population and 27,4% of the randomised population) questionnaires were collected (male=133), from 51 Health Centres (87,9% of the randomised and 56,3% of all the Health Centres). The more quoted information sources on medicines were Journals (49,0%), Text Books (49,0%), Pharmaceutical Industry (44,4%), Simposium Terapêutico (42,4%), Prontuário Terapêutico (38,6%), the Resumo de Características dos Medicamentos (Medicines Characteristics Synopsis) (38,3%), Information from Congresses (37,7%), Information from an Expert Doctor (14,6%), Internet search (1,1%) and Information by a colleague from a Health Centre (6,6%). For 114 respondents (35,9%) there were no service meetings to discuss medical history records and therapeutics issues and for n=227 (72,7%) respondents there is no interest in discussing therapeutic issues with community pharmacists. Conclusions: These results emphasize the importance of written material as a source of medicines information, though independent and credible sources like the Portuguese Prontuário Terapêutico and the Resumo de Características dos Medicamentos are not cited as frequently as expected. There is need to perform medical meetings inside the Health Centre to discuss clinical matters and therapeutics.